Changes in Japanese Pharmacists' Recognition of Their Role in Community Public Health before and after the Spread of COVID-19 - Kayoko Takeda Mamiya; Akari Yoshida (MDPI AG, 2021)
Background: In our previous study regarding infection prevention after COVID-19, many Japanese citizen respondents had not received education/training on infection prevention. However, a total of 47.7% (n = 143) of these respondents wanted to receive education from healthcare professionals regarding the methods and effects of infection prevention. Therefore, changes in recognition of the roles of Japanese pharmacists before and after COVID-19 were investigated. Methods: We conducted a survey to determine whether recognition of Japanese pharmacists' roles, especially their role in public health in the community, changed after COVID-19. Results: A total of 93.9% (n = 307) of the pharmacist respondents showed an increased awareness of infection prevention. Before COVID-19, the hospital pharmacists (67.2%; n = 80) were more aware of infection prevention than were pharmacy pharmacists (51.7%; n = 74) and drugstore pharmacists (47.7%; n = 31). The number of pharmacists who felt that the role of pharmacists in the community had changed after the pandemic increased, but the numbers of community pharmacy pharmacists (51.8%; n = 74) and drugstore pharmacists (55.4%; n = 36) were found to be slightly higher than those of hospital pharmacists (47.9%; n = 57). Conclusions: In a society in which swift responses and changes are required, for individuals to work as medical personnel their ability to respond while always being aware of the needs of society is required now more than ever.